The Way Forward for Social Safety Nets in Burkina Faso - Vandeninden, Frieda; Grun, Rebekka; Semlali, Amina (World Bank, Washington, DC, 2019)
The government of Burkina Faso has a strong interest in strengthening its social safety nets provision to better support the country’s poorest and most vulnerable households. It has demonstrated this commitment through past investments in social protection. Against a backdrop of limited public finances and budgetary constraints, it is critical to ensure that the resources allocated for social protection, and for social safety nets, are cost-effective. This report responds to a request by the Burkinabe Ministry of Finance to: enhance knowledge about the current state of social safety nets and assess their effectiveness in meeting the needs of the poor; and inform a debate on feasible reform and policy options to make social safety nets in Burkina Faso more effective and of greater impact and able to contribute to a consolidation of expenditure.